ЗА ПРОСВЕТНИТЕ ВЛИЈАНИЈА ВО МАКЕДОНИЈА (1878-1903) - Silvana Sidorovska-Chupovska (Philological Studies, 2019)
This paper explores the educational influences in Macedonia after the Eastern Crises (1875-1881). Namley, for a long period of time, the Ottoman Turkish government supported Greek religious and educational propaganda on the territory of Macedonian. Even so, after 1878, Macedonia was the country where the propaganda interests, at the level of education, were mostly Bulgarian and Serbian in nature. These, in turn, had a different success in the field during their twenty-five year span.